PENGARUH PROMOTION MIX DAN KUALITAS PELAYANAN TERHADAP CUSTOMERS TRUST SERTA DAMPAKNYA PADA LOYALITAS PELANGGAN KONSUMEN TOKO DAN SWALAYAN DI ACEH BARAT - Ivon Jalil (JURNAL EKOMBIS, 2018)
With the increasing intensity of competition among retailers franchises that have the capital, resources and extensive network, will have an impact that is also quite significant for local retailers, which are managed and run directly by the owner. Most traditional stores are still using the old ways of doing business and not taking advantage of technology to support its efforts in improving the productivity and quality of service. It is not possible traditional retailers will eventually be abandoned buyers. In the city of Calang and Meulaboh, the retail industry is also experiencing the same thing. Although numerous customers, but their spending patterns do not settle in one shop. Most of them are always moving from one shop to another. Because the CR above 1.96 and P <0.05, then Ho is rejected and H1 accepted, which means no significant relationship (significant) between independent and dependent construct, either directly or indirectly through variable between.Keywords: Customers Trust, Customer Loyalty, Consumer Stores, Promotion Mix, Quality of Service, And Supermarkets